Twit : the owl who wasn't wise - Cole ,Stephen; Illustrator, Jane Porter (London, Orion Children's Books, 2013)
Twit is a raggedy little owl whose brothers love to play tricks on him. It gets him into all sorts of trouble! But that all changes when Twit meets Norma, a clever little vole. All of a sudden, Twit's brothers had better watch out - Norma and Twit might just have a trick of their own to play.
A1 shelf
Keywords: English Fiction story book